2018
DOI: 10.1093/hmg/ddy098
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the mitochondrial ribosomal protein MRPS22 lead to primary ovarian insufficiency

Abstract: Primary ovarian insufficiency (POI) is characterized by amenorrhea and loss or dysfunction of ovarian follicles prior to the age of 40. POI has been associated with autosomal recessive mutations in genes involving hormonal signaling and folliculogenesis, however, the genetic etiology of POI most often remains unknown. Here we report MRPS22 homozygous missense variants c.404G>A (p.R135Q) and c.605G>A (p.R202H) identified in four females from two independent consanguineous families as a novel genetic cause of PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…All of the RNA components of the mitochondrial translation machinery are encoded in mtDNA, the protein components of the ribosome and accessory proteins such as aminoacyl tRNA synthetases being nuclearly encoded. Mutations in nuclear genes encoding protein components of the ribosome affect the accuracy of translation and are associated with a diverse range of pathologies including ovarian insufficiency [ 260 ], encephalopathy [ 261 ], Leigh syndrome [ 262 ] and stress related behavioral alterations in mice [ 263 ]. A similar diversity of presentation is seen in mutations affecting mitochondrial aminoacyl tRNA synthetases and the reasons for this diversity from an apparently similar mechanism are discussed by González-Serrano [ 264 ].…”
Section: Genetics Of Mitochondrial Dnamentioning
confidence: 99%
“…All of the RNA components of the mitochondrial translation machinery are encoded in mtDNA, the protein components of the ribosome and accessory proteins such as aminoacyl tRNA synthetases being nuclearly encoded. Mutations in nuclear genes encoding protein components of the ribosome affect the accuracy of translation and are associated with a diverse range of pathologies including ovarian insufficiency [ 260 ], encephalopathy [ 261 ], Leigh syndrome [ 262 ] and stress related behavioral alterations in mice [ 263 ]. A similar diversity of presentation is seen in mutations affecting mitochondrial aminoacyl tRNA synthetases and the reasons for this diversity from an apparently similar mechanism are discussed by González-Serrano [ 264 ].…”
Section: Genetics Of Mitochondrial Dnamentioning
confidence: 99%
“…The String analysis showed that miR-1260a was mostly associated with the ribosomal protein family effective in translation. There are some studies in the literature investigating the effects of this protein family of the development of ovarian cancer [37,38]. The results of this studies showed that the ribosomal proteins had signi cant and critical functions in the development of ovarian cancer, and therefore was emphasized to provide information on the pathophysiology, and treatment of ovarian dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in the literature investigated the effects of this protein family on the development of ovarian cancer [37,38]. These studies showed that ribosomal proteins had signi cant, and critical functions in the development of ovary, and therefore may provide data about the pathophysiology, and treatment of ovarian dysfunctions.…”
Section: Roc Analysismentioning
confidence: 99%
“…Whole exome sequencing (WES) of two patients from Family I was performed using DNA (1µg) extracted from whole blood and fragmented and enriched using the Truseq DNA PCR Free kit (Illumina). Samples were sequenced on a HiSeq2500 (Illumina) with 2x100bp read length and analyzed as described (Chen et al, 2018). Raw fastq files were mapped to the reference human genome GRCh37 using BWA (Li and Durbin, 2009) (v.0.7.12).…”
Section: Methodsmentioning
confidence: 99%